P29 Is workforce participation detrimental to the mental health of women andchildren? Evidence from six waves of data from the longitudinal study of australian children. (3rd September 2019) - King, TL; Shields, M; Byars, S; Craig, L; Milner, A
Abstract : Background: The past 50 years has been marked by the increasing participation of women in the workforce. There is some evidence that this expansion of women into the workforce may impose a mental health burden on women, and it is popularly speculated that children are also adversely affected. This analysis aimed to examine the associations between household workforce participation (household employment configuration) on the mental health of mothers and children Methods: Six waves of data from the Longitudinal Study of Australian Children were used, from 2004 (when children were aged 4–5 years) to 2014 (age 14–15 years). Mental health outcome measures were the Strengths and Difficulties Questionnaire scores for children and adolescents, and the Kessler-6 score for mothers. A five-category measure of household employment configuration was derived from parent report (dual full time; male breadwinner; female breadwinner; shared employment (both part-time); father full time/mother part time). Mundlak models were used to compare within- and between-person effects after controlling for confounders including mother's country of birth; mother's indigenous status; mother's education; mother's occupation; area disadvantage; household income; mother's age; number of children in household; presence of child under 5 years; maternal mental health (in child models); and child mental health (in maternal models). Models were restricted to those households in which household employment configuration changed, with the reference category being the father full time/mother part time configuration. Results: There were no within-person effects of employment configuration on maternal mental health, however between-person effects indicated that women in a male breadwinner household had poorer mental health than women in a father full time/mother part time household (ß 0.63, 95%CI 0.02–1.24). There were no between- or within-person effects for children/adolescents. Conclusion: These results counter prevailing social attitudes regarding women's workforce participation by demonstrating that children are not adversely affected by their mother's workforce participation, nor are they disadvantaged by the extent of this participation. Also contrary to normative social expectations, women in traditional 'male breadwinner' household configurations experience poorer mental health than those in a 'father full-time/mother part-time' arrangement. Importantly too, no adverse mental health effects were observed in women working full time, either as a breadwinner or in a dual full-time arrangement (where both partners work full time). These results are important in demonstrating that increasing women's workforce participation is not detrimental to the mental health of either themselves, nor their children.